2014
DOI: 10.1186/2110-5820-4-3
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of cisatracurium in the intensive care unit: an observational study

Abstract: BackgroundData from previous studies indicate that optimal conditions for intubation are met 120 seconds after administration of 0.15 mg.kg-1 cisatracurium (ED95 × 3) following the induction of anesthesia. The aim of this study was to compare the doses required for complete paralysis after induction of anesthesia in ICU patients with the dose used in patients undergoing elective surgery.MethodsSeventeen ICU patients undergoing percutaneous tracheostomy and 17 patients undergoing an elective surgical procedure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…When there is a specific indication for NMBAs, adequate analgesia and sedation should be provided [ 39 ]. Furthermore, the depth of blockade should be monitored [ 40 ], and the duration should be kept as short as possible (Table 17 (Tab. 17) ).…”
Section: Management Of Delirium Analgesia and Sedation In Adult Intmentioning
confidence: 99%
“…When there is a specific indication for NMBAs, adequate analgesia and sedation should be provided [ 39 ]. Furthermore, the depth of blockade should be monitored [ 40 ], and the duration should be kept as short as possible (Table 17 (Tab. 17) ).…”
Section: Management Of Delirium Analgesia and Sedation In Adult Intmentioning
confidence: 99%
“…The pharmacokinetics of NMBAs in critically ill patients can be affected by many conditions, such as sepsis and/or shock [12]. In addition, it has been shown that ICU patients are less sensitive to neuromuscular blockade than patients in the operating room [14]. …”
Section: Discussionmentioning
confidence: 99%
“…The benefits and limitations of TOF stimulation were primarily determined from studies performed in operative room patients [10, 11], with results that may not be generalizable to ICU patients. In critically ill patients, the duration of neuromuscular blockade is longer, sepsis and/or shock is often present, and pharmacokinetic is difficult to predict [1214]. Lastly, agreement between subjective and objective means of assessing the degree of neuromuscular blockade has been little studied in ICU [15–17].…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 33 patients requiring neuromuscular blockade for ventilation in the ICU, using atracurium via a peripheral vein, phlebitis was observed in two patients 9. Both atracurium and cisatracurium are non-depolarising muscle relaxants from the benzylisoquinoline family that undergo degradation in plasma at physiological pH and temperature by organ-independent Hofmann elimination 10. Cisatracurium is a stereoisomer of atracurium and as such has the same molecular weight 11.…”
Section: Discussionmentioning
confidence: 99%